1982
DOI: 10.3382/ps.0611594
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Forced Molt Period on Postmolt Performance of Leghorn Hens

Abstract: Sixty-four-week-old Single Comb White Leghorn (SCWL) hens were subjected to the following treatments: 1) no forced molt (control); 2) forced molt for 4 weeks (FM 4 ); 3) forced molt for 6 weeks (FM 6 ): and 4) forced molt for 8 weeks (FM 8 ). Molt was induced by restricting feed, water, and photoperiod. Data were analyzed at the 5% level of probability.During the early postmolt period (72 to 76 weeks of age), birds in all FM groups consumed significantly more feed and had significantly higher hen-day egg produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1
2

Year Published

1986
1986
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(21 citation statements)
references
References 9 publications
1
17
1
2
Order By: Relevance
“…production rates associated with molted secondcycle hens are higher than those of nonmolted hens of the same age [2, 4,7].…”
mentioning
confidence: 99%
“…production rates associated with molted secondcycle hens are higher than those of nonmolted hens of the same age [2, 4,7].…”
mentioning
confidence: 99%
“…Egg output was less when body weight losses of either less than 65% or greater than 80% occurred. Lee (1982) also compared different periods of food restriction, but found they had no significant effect on post-moult egg production. However the three periods he tested (3, 5 and 7 weeks following 7 d of food withdrawal resulted in body weight reductions of only 89, 85 and 91% of initial body weight respectively.…”
Section: Discussionmentioning
confidence: 96%
“…Previous investigations indicated that varying the duration of induced moults altered shell strength (Baker et al 1982, Lee, 1982. The moulting procedures we compared may have all allowed for an optimum or equal regression and regeneration of the uterus and so no differences in egg shell quality were obtained.…”
Section: Discussionmentioning
confidence: 97%
“…Kehilangan berat badan itik yang tidak mendapat perlakuan pemuasaan P0 hanya mendapat perlakuan pembatasan ransum selama 20 hari mengalami kehilangan berat badan 16,52 % sedangkan yang mendapat perlakuan pemuasaan 12 hari adalah yang paling besar mencapai 28,44 %. Menurut Lee (1982) lamanya force molting pada unggas dapat mempengaruhi tingkat penurunan berat badan, dan pemuasaan yang lebih lama akan menurunkan berat badan lebih besar dibanding pemuasaan yang lebih singkat.…”
Section: Materi Dan Metodeunclassified